The Effect of The Numbered Head Together Learning Model on The Student's Biology and Character Learning Outcomes in The Principles of The Respiratory System in Class XI SMA Negeri 1 Panai Hulu - Ismi Nur Hasmi; Zunaidy Abdullah Siregar (Budapest International Research and Critics University, 2022)
This study aims to determine; the influence of the Numbered Head Together learning model on learning outcomes and student character on the subject of the respiratory system at SMA Negeri I Panai Hulu, The research method uses a quasi-experimental method with a research sample of 2 classes that are determined randomly with cluster random sampling technique taught by learning model Numbered Head Together type cooperative. And 1 class is taught using conventional learning strategies while 1 class is taught using the Numbered Head Together learning model on learning outcomes and student character on the subject of the respiratory system. The research instrument used a learning outcome test of 30 questions in the form of multiple choice; student discipline character test as many as 20 questions and the questions have been tested for validity. The results showed: There was a significant effect between the use of the Numbered Head Together type of cooperative learning model on learning outcomes and student character on the subject of the respiratory system at SMA Negeri I Panai Hulu. Biology learning outcomes of students who are taught by cooperative learning model type Numbered Head Together 87.60 ± 3.30. and Discipline Characters Students who are taught by cooperative learning model Numbered Head Together are 86.51 ± 2.59.